PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DI SMP ALETHEA JEMBER - Sarah Ayu Asari Situmorang (Sekolah Tinggi Teologi Duta Panisal, 2020)
The research in this article is motivated by the importance of learning styles in classroom learning activities. In general, learning styles are divided into 3, namely: visual learning styles that use visual sensory, audiotory learning styles that use hearing sensory, and kinesthetic learning styles that use physical sensory movements. The third learning style has a very important role because it is one of the determinants of learning outcomes in the learning process. The learning style used and referred to in this study is the visual learning style. The formulation of the problem in this study are (1) Is there an influence of learning styles on student learning outcomes in Christian Religious Education in Alethea Jember Middle School? (2) Is there a relationship between learning styles and student learning outcomes in Christian Religious Education in Alethea Jember Middle School? (3) What is the percentage of the influence and relationship of learning styles on student learning outcomes in Christian Religious Education in Alethea JemberMiddle School? The hypotheses in the study are (1) There is an Influence of Learning Style on Student Learning Outcomes in Christian Religious Education Subjects at Alethea Jember Middle School. (2) There is a Relationship between Learning Style and Learning Outcomes in Christian Religious Education. (3) The influence and relationship of learning styles on student learning outcomes in Christian Religious Education subjects at Alethea Jember Middle School is very significant, which is around %. The method used by researchers is a quantitative method with research design Design One Shoot Case Study Experiment. This design is used because there is a group that is given treatment (treatment). Data collection techniques used by researchers are questionnaires (questionnaire). While the data analysis technique used to test hypotheses is simple linear regression with the help of IBM SPSS Statistics